Restauration de Sapho ou Le Chant de Raoul Verlet - Lucie Courtiade (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The study of Sapho ou Le Chant, a plaster cast foundry created by Raoul Verlet and preserved in the Angoulême Museum since 1926, has allowed to approach a common problematic, that one of split plaster cast by the expansion of steel reinforcements corrosion, caused by high humidity conservation conditions. The main intervention concerned the fragments reconstruction requiring the design and the execution of a stainless steel pedestal. The structural interventions was completed with simple and reinforced stickings of the larger fragments.